If it's not what You are looking for type in the equation solver your own equation and let us solve it.
abs(x+3)+abs(x-1) < 5
((sin(x^3))^tan(x^2))^sin(x^(x^3))
((sin(x^3))^tan(x^2))^sin(x)
22;7500;22;7600;0;0
7 = m/125
| 2sin^2-3cos+1=0 | | 11a^2+2a-17=0 | | 5a+6a=-6+8a | | 360=(x+40)+(4x+70)+(2x+110) | | x+47=54 | | 4x^2-2-8w=-6x | | -14x+1=21 | | 360=(x+50)+(2x+80)+(4x+20) | | x^4-5x^3-2x^2-3x-9= | | 5y-(3y+8)=3-(7y-9) | | 5(x-1)=3(2-x)-5 | | x+52=61 | | 11v-2v=54 | | x+78=86 | | 90x^2-63xy+18x=0 | | 7=m/125 | | -3.5b-1.75c= | | 4X+20=25-x | | x-2(-2x+20)=20 | | c/2=-14 | | X^2+27x-18=0 | | d=7.25t | | 1.1x=94000 | | -4(2t+5)=-60 | | 24x+7x=19 | | =11x+5y-30z | | 2^3x=1/8 | | -10(s+4)=-78 | | 2.5=0.6*[19.6(1-.61*x)]^(1/2)*2*x | | 324x^4-4y^4= | | 2/386/7 | | x/3-4#8 |